Bisphosphonate Treatment Modifies Canine Bone Mineral and Matrix Properties and their Heterogeneity - Gourion-Arsiquaud, Samuel (2009)
Bone loss and alterations in bone quality are major causes leading to bone fragility in postmenopausal women. Although bisphosphonates are well known to reduce bone turnover and prevent bone loss in postmenopausal osteoporosis, their effects on other bone properties are not fully characterized. Changes in bone mineral and matrix properties may contribute to the anti-fracture efficacy observed with bisphosphonate treatments. The aim of this work was to analyze the effect of a one-year treatment with either alendronate or risedronate, at low and high doses, on spatially resolved bone material and compositional properties that could contribute to the fracture efficacy of these agents. Distal tibias from thirty normal beagles that had been treated daily for one year with oral doses of vehicle (Veh), alendronate (Aln) at 0.2 or 1 mg/kg, and risedronate (Ris) at 0.1 or 0.5 mg/kg were analyzed by Fourier Transform Infrared imaging (FTIRI) to assess the changes in both mineral and matrix properties in discrete bone areas. The widths at half maximum of the pixel histograms for each FTIRI parameter were used to assess the heterogeneity of the bone tissue. Aln and Ris increased the mineral content and the collagen maturity mainly in cancellous bone and at the endocortical surface. Significant differences were observed in the mineral content and in the hydroxyapatite crystallinity distribution in bone tissue, which can contribute to reduced ductility and micro-crack accumulation. No significant differences were observed between low and high dose nor between Aln and Ris treatments. These results show that pharmacologic suppression of bone turnover increases the mineral and matrix bone tissue maturity in normal cancellous and endocortical bone areas where bone turnover is higher. These positive effects for decreased fracture risk are also associated with a loss of bone heterogeneity that could be one factor contributing to increased bone tissue brittleness and micro-crack accumulation.